A COMPARATIVE STUDY BETWEEN OPEN CHOLECYSTECTOMY VERSUS LAPAROSCOPIC CHOLECYSTECTOMY - HARSANA, BALRAM; JAIN, PIYUSH (International Journal of Current Pharmaceutical Research, 2024)
Objective: This study aims to evaluate the comparative effectiveness of laparoscopic cholecystectomy (LC) versus open cholecystectomy (OC) in terms of surgery duration, blood loss, postoperative discomfort, hospital stay length, cost-effectiveness, and patient satisfaction. It also assesses differences in primary outcomes, such as mortality, complications, and symptom relief, as well as secondary outcomes, including conversion rates, operative time, and recovery. Methods: We conducted a prospective observational study involving 200 patients aged 10-70 with symptomatic gallstones confirmed via ultrasonography at Somani Hospital, Jaipur, from July 2021 to August 2023. Patients were randomly assigned to undergo either lC or OC. We collected data on surgical duration, blood loss, postoperative pain, hospitalization period, and complications, among other variables. Statistical analysis was performed using software tools. Results: Our study involved 200 patients, predominantly female (77%). The average duration of lC was shorter (67.37 min) compared to OC (93.95 min). lC patients had a shorter average hospital stay (2.8 d) compared to OC patients (5.1 d). The conversion rate from lC to OC was 6%, primarily due to anatomical and technical challenges. Complications were significantly lower in lC (17%) compared to OC (28%). Conclusion: lC is more efficient, entails fewer complications, and leads to a quicker recovery and shorter hospital stay compared to OC, supporting its preference in surgical practice for eligible patients with symptomatic gallstone disease. The lower rate of complications and shorter recovery time suggest that lC should be the standard care for cholecystectomy where feasible.